2020
DOI: 10.1007/s10286-020-00714-0
|View full text |Cite
|
Sign up to set email alerts
|

The extended autonomic system, dyshomeostasis, and COVID-19

Abstract: The pandemic viral illness COVID-19 is especially life-threatening in the elderly and in those with any of a variety of chronic medical conditions. This essay explores the possibility that the heightened risk may involve activation of the "extended autonomic system" (EAS). Traditionally, the autonomic nervous system has been viewed as consisting of the sympathetic nervous system, the parasympathetic nervous system, and the enteric nervous system. Over the past century, however, neuroendocrine and neuroimmune s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
100
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(114 citation statements)
references
References 195 publications
1
100
0
5
Order By: Relevance
“…Despite the many difficulties associated with the global COVID-19 pandemic, the year 2020 was a good one for Clinical Autonomic Research, and the prospects for 2021 are even better. During 2020, the journal published special issues and articles on the autonomic aspects related to COVID-19 [ 2 , 5 , 7 , 10 , 12 , 13 ]. All COVID-19-related manuscripts are Open Access immediately upon publication.…”
mentioning
confidence: 99%
“…Despite the many difficulties associated with the global COVID-19 pandemic, the year 2020 was a good one for Clinical Autonomic Research, and the prospects for 2021 are even better. During 2020, the journal published special issues and articles on the autonomic aspects related to COVID-19 [ 2 , 5 , 7 , 10 , 12 , 13 ]. All COVID-19-related manuscripts are Open Access immediately upon publication.…”
mentioning
confidence: 99%
“…Autonomic function testing is essential for detection, quantification, and localization of autonomic dysfunction of several medical conditions, and are relevant to diagnosis, prognosis, and clinical management of patients to improve their quality of life [ 1 ]. Furthermore, some have hypothesized that the autonomic nervous system is involved in the pathophysiology of COVID-19 [ 4 , 5 ], and that autonomic dysfunction could be part of the spectrum of long-term sequelae in survivors, known as “long-haul COVID” [ 8 ]. If this is true, referral for autonomic testing would be expected to rise soon.…”
mentioning
confidence: 99%
“…SARS-CoV-2 infection can increase sympathetic activity via changes in blood gases and immunoinflammatory factors ( Porzionato et al, 2020 ). Autonomic activation has direct adrenergic effects on RAAS, which increases aldosterone secretion and contributes to the loss of K + ( Darbar et al, 1996 ; Goldstein, 2020 ; Gordon et al, 1967 ; Nayyar et al, 2017 ). One study also showed a relationship between the mortality of COVID-19 patients with increased plasma cortisol levels ( Tan et al, 2020 ).…”
Section: Neuroendocrine Control Of Hydroelectrolytic Balancementioning
confidence: 99%